Field emission from two-dimensional GeAs. (22nd December 2020) - Di Bartolomeo, Antonio; Grillo, Alessandro; Giubileo, Filippo; Camilli, Luca; Sun, Jianbo; Capista, Daniele; Passacantando, Maurizio
Abstract: GeAs is a layered material of the IV–V groups that is attracting growing attention for possible applications in electronic and optoelectronic devices. In this study, exfoliated multilayer GeAs nanoflakes are structurally characterized and used as the channel of back-gate field-effect transistors. It is shown that their gate-modulated p-type conduction is decreased by exposure to light or electron beam. Moreover, the observation of a field emission (FE) current demonstrates the suitability of GeAs nanoflakes as cold cathodes for electron emission and opens up new perspective applications of two-dimensional GeAs in vacuum electronics. FE occurs with a turn-on field of ∼80 V μ m − 1 and attains a current density higher than 10 A c m − 2, following the general Fowler–Nordheim model with high reproducibility.